Interstitial pneumonitis secondary to intravesical bacillus calmette-guerin for carcinoma in-situ of the bladder - Eric K. Diner; Mohan Verghese (International Brazilian Journal of Urology, 2004)
We report an 81-year-old male who developed severe interstitial pneumonitis on maintenance intravesical Bacillus Calmette-Guerin (BCG) for in-situ carcinoma of the bladder. The patient was treated with steroids and anti-tuberculin therapy with complete response. While there is no established standard of care for the treatment of interstitial pneumonitis, recent reports describe success with combination of corticosteroids and anti-tuberculin medications. We elected to follow this precedent and treated our patient with corticosteroids and anti-tuberculin therapy with good outcome.